Specificity of Dysfunctional Beliefs in Children with Social Anxiety Disorder: Effects of Comorbidity. Issue 4 (4th July 2022) - Mobach, Lynn; Klein, Anke M.; Schniering, Carolyn A.; Hudson, Jennifer L.
ABSTRACT: Objective : This study examined the content-specificity of dysfunctional social beliefs to Social Anxiety Disorder (SoAD) in a large, clinically referred sample of children with a variety of anxiety, mood and externalizing disorders. The effects of comorbidity on the content-specificity of dysfunctional social beliefs were examined. Method : Participants included 912 children aged 7–12 years ( M age  = 9.15; 45.5% female) who presented at a specialized clinic for assessment and treatment of anxiety disorders. Children with SoAD were compared to children with nonsocial anxiety disorders, children with SoAD and mood disorders, and children with SoAD and externalizing disorders, on self-reported dysfunctional social threat beliefs, physical threat, hostility, and personal failure beliefs. Results : Children with SoAD endorsed significantly higher levels of dysfunctional social threat beliefs when compared to children with nonsocial anxiety disorders. However, children with SoAD and mood comorbidity scored significantly higher on dysfunctional social beliefs than all other groups. Conclusions : Results suggest that within childhood anxiety disorders, dysfunctional social beliefs are content-specific for SoAD. Externalizing comorbidity does not seem to change the level of dysfunctional social beliefs in this group. However, mood comorbidity leads to endorsement of higher levels of dysfunctional social beliefs. These results provide support for, and refine, the content-specificity hypothesis and highlight the importance of taking comorbidity into account when examining and treating dysfunctional beliefs in youth.